Pembiayaan Pendidikan Berbasis Kinerja dan Penguatan Pendidikan Masyarakat (Studi Implementasi BOS Kinerja pada Sekolah Menengah Atas di Papua) - Ningsih, Nur; Syafriadi, Syafriadi; T, Musdalifa; Khasanah, Rohmatun; Abdullah, Rahibun (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Educational inequality in Indonesia’s frontier, outermost, and disadvantaged (3T) regions remains a major challenge, particularly in Papua where education development indicators lag behind the national average. To address this issue, the government introduced the Performance-Based School Operational Assistance (BOS Kinerja) program as an incentive for schools to improve quality through better management and academic outcomes. This study aims to evaluate the implementation of BOS Kinerja in senior high schools (SMA) in Papua and to identify its impacts, challenges, and opportunities for improvement. Using a descriptive qualitative approach, data were collected through interviews with principals, teachers, and school committees, complemented by observations and document analysis in four recipient schools located in Jayapura and Mimika Regencies. The findings indicate that BOS Kinerja supports teacher professional development, instructional innovation, and student engagement, particularly in schools with strong leadership and participatory governance. Nevertheless, significant obstacles remain, including limited human resources, delayed fund disbursement, geographical constraints, and performance indicators that are not fully context-sensitive. Strengthening digital financial management, enhancing school leadership capacity, and fostering community participation and cross-sector partnerships are identified as key strategies for ensuring more effective and sustainable implementation of BOS Kinerja in Papua.